Plasma retinol, carotene and vitamin E concentrations and lung function in a crocidolite-exposed cohort from Wittenoom, Western Australia: a cohort study - Alfonso, Helman; Fritschi, L.; De Klerk, N.; Ambrosini, G.; Beilby, J.; Olsen, N.; Musk, A. (BioMed Central, 2005)
BackgroundIncreased rates of death from asbestos related diseases have been reported for people previously employed in the mining and milling operations at Wittenoom (Western Australia), and people who lived in the nearby town, where they were environmentally exposed to crocidolite.MethodsAnnual measurements of forced expiratory volume in 1 second (FEV1) and forced vital capacity (FVC) and plasma concentrations of retinol, carotene and vitamin E have been made since 1992. Mixed effects models were used to examine the associations between lung function and the plasma vitamin levels of retinol, carotene and vitamin E.ResultsAfter adjusting for potential confounders, higher plasma retinol and carotene concentrations were significantly associated with higher levels of lung function at entry into the study, while vitamin E concentrations were associated with lower entry lung function. Retinol was associated with a less steep decline of lung function over time, while carotene concentrations were associated with an increased decline of lung function over time and vitamin E levels were not associated with changes of lung function over time.ConclusionThese results support a beneficial relationship between plasma concentrations of retinol on the levels and rates of change of lung function, while showing no such consistent beneficial effect for plasma levels of beta-carotene or vitamin E.